Glimpses of Eugenics in Ayurveda WSR to Preconceptional and Antenatal Remedies - Yogita Shrivas1 , Sujata Shamkuwar2 , Rekha Shinde3 , Arpita Jaiswal4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Every parent wish to have a good progeny. Improvement is basic human nature. Hence eugenics emerged in20th century as a movement in many countries which had its own pros and cons with serious ethical concerns.Though conception is a natural and physiological phenomenon, Ayurveda advocates that conception shouldnot be accidental, rather it must be planned. The planning includes preparation of body as well as mind.To fulfil the wish of getting a good progeny Ayurveda texts mention a detailed framework to be followed.It includes pre-conceptional preparation to be executed by the couple and anti-natal care of pregnant lady.This is uniform and open to all aspirant parents without any selective bias. It is purely aimed at achievinga healthy and intelligent future generation irrespective of any race, cast and creed. The unbiased holisticapproach of Ayurveda brings out positive aspect of eugenics to the society